2015
DOI: 10.3389/fimmu.2015.00440
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Recombinant scFv Antibodies Generated Against Hemagglutinin Protein of Influenza A Virus

Abstract: Human influenza A viruses have been the cause of enormous socio-economic losses worldwide. In order to combat such a notorious pathogen, hemagglutinin protein (HA) has been a preferred target for generation of neutralizing-antibodies as potent therapeutic/diagnostic agents. In the present study, recombinant anti-HA single chain variable fragment antibodies were constructed using the phage-display technology to aid in diagnosis and treatment of human influenza A virus infections. Spleen cells of mice hyper-immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A recent study demonstrated the diagnostic potential of recombinant scFv antibodies generated against the hemagglutinin protein of influenza A virus for diagnosis and treatment of human influenza A virus infections. In that study, an ELISA was developed that demonstrated 83.9% sensitivity and 100% specificity for H1N1 influenza A viruses and promised to be a cheaper alternative to the costly RRT-PCR test [68]. At research institutes and in reference or hospital laboratories, where sophisticated equipment is available, electron microscopy, cytology and histology may also be used to diagnose influenza virus infections.…”
Section: Laboratory Diagnosis Of Influenzamentioning
confidence: 99%
“…A recent study demonstrated the diagnostic potential of recombinant scFv antibodies generated against the hemagglutinin protein of influenza A virus for diagnosis and treatment of human influenza A virus infections. In that study, an ELISA was developed that demonstrated 83.9% sensitivity and 100% specificity for H1N1 influenza A viruses and promised to be a cheaper alternative to the costly RRT-PCR test [68]. At research institutes and in reference or hospital laboratories, where sophisticated equipment is available, electron microscopy, cytology and histology may also be used to diagnose influenza virus infections.…”
Section: Laboratory Diagnosis Of Influenzamentioning
confidence: 99%
“…Numerous scFvs have been constructed against haptens, 53 proteins, 54 carbohydrates, 55 receptors, tumor antigens, 56 and viruses. 57 All of these scFvs are good for use in many areas, such as medical therapies and diagnostic applications. In our studies, we used a B/T cell conserved influenza viral epitope to target activating cellular receptors.…”
Section: Single-chain Variable Antibody Fragmentsmentioning
confidence: 99%
“…Carnell et al reviewed comprehensive methods for influenza virus neutralization assays, based on the pseudotype viral particles, which utilize chimeric viruses bearing influenza glycoproteins, and depict how such assays can replace the traditional HA neutralization assays for the evaluation of new age influenza vaccines ( 18 ). To detect the incidence of Influenza virus with high efficiency and accuracy, Rajput et al generated HA specific high affinity recombinant single chain variable fragment (scFv) antibodies showing high sensitivity (83.9%) and specificity (100%) for three different strains of influenza virus ( 19 ).…”
mentioning
confidence: 99%